1998
DOI: 10.1007/bf02386312
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trace elements in human head hair by neutron activation analysis

Abstract: Instrumental neutron activation analysis was used to measure concentrations of elements in hair samples from a group of patients of a medical clinic and from a control group. Elements A1, As, Br, Ca, Cd, C1, Co, Cu, Fe, Hg, K, Mg, Mn, Na, Sb, Sc, Se, V and Zn were analyzed and comparisons were made between the results obtained for these two groups of individuals. Normal ranges for elemental hair by commercial laboratories are also presented, for comparison, with those results obtained for the control group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 5 publications
1
8
0
3
Order By: Relevance
“…The diŠerence between certiˆed and measured values for Na, Mg, Ca and Cu might be due to low counting statistics. Each element such as Al, Cl and V, whose certiˆed value was not available, showed good agreement with those by Saiki et al 20) .…”
Section: Validation Of Analytical Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…The diŠerence between certiˆed and measured values for Na, Mg, Ca and Cu might be due to low counting statistics. Each element such as Al, Cl and V, whose certiˆed value was not available, showed good agreement with those by Saiki et al 20) .…”
Section: Validation Of Analytical Methodssupporting
confidence: 80%
“…5 Human Hair CRM was performed by INAA in order to ascertain the accuracy of the method. Results are presented in Table 2 20) even though involving uncertainties of 25 and 24, respectively. The diŠerence between certiˆed and measured values for Na, Mg, Ca and Cu might be due to low counting statistics.…”
Section: Validation Of Analytical Methodsmentioning
confidence: 99%
“…Studies showed that scalp hair can record the level and changes of many elements in the body over a long period of time (Saiki et al 1998). Changes in the elemental composition of hair are believed to depend on alterations of external and internal media of the human body, and it is considered that the hair of healthy individuals contains each element within a well defined range of concentration (Kolmogorov et al 2000;Man et al 1996), and it can be considered as a potential indicator of both external and internal longterm exposure to environmental pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Manganese concentration in hair and fingernails with respect to age is as shown in Fig.3 Manganese levels in both hair and fingernails decreased with age, but the decrease is pronounced in hair, indicating that manganese may be playing some physiological functions (Hull, 2003). Scalp hair and fingernails can record the level and changes of elements in the body over a long period of time (.Saiki et al,1998;Khuder et al,2008) Changes in the elemental composition of hair therefore depend on alterations of external and internal media of the human body, and it is considered that hair and fingernails of healthy individuals contain each element within a well defined range of concentration and may be considered as a potential indicator of both external and internal long term exposure to pollutants. The idea of hair and fingernail analysis is inviting, since it is painlessly removed, normally discarded, easily stored and transported to the laboratory for analysis.…”
Section: Pearson Parametric Correlationmentioning
confidence: 96%